Assessment of agonistic and antagonistic properties of widely used oral care antimicrobial substances toward steroid estrogenic and androgenic receptors - Michalíková, Klára; Linhartová, Lucie; Ezechiáš, Martin; Cajthaml, Tomáš (Chemosphere, 2019)
Personal care product consumption has increased in the last decades. A typical representative ingredient, i.e., triclosan, was identified in the scientific literature as an endocrine disruptor, and its use is restricted in several applications. Oral hygiene formulations contain various compounds, including synthetic phenol derivatives, quaternary ammonium compounds (QACs), various amides and amines, or natural essential oils containing terpenes. The aim of this paper was to explore possible endocrine-disrupting effects of these most-used compounds. For this purpose, two different assays based on recombinant yeast (BMAEREluc/ERα; BMAEREluc/AR) and human cell lines (T47D; AIZ-AR) were employed to investigate the agonistic and antagonistic properties of these compounds on human estrogen and androgen receptors. The results showed that none of the compounds were indicated as agonists of the steroid receptors. However, octenidine (OCT, QAC-like) and hexadecylpyridinium (HDP, QAC) were able to completely inhibit both androgenic (IC50 OCT = 0.84 μM; IC50 HDP = 1.66 μM) and estrogenic (IC50 OCT = 0.50 μM; IC50 HDP = 1.64 μM) signaling pathways in a dose-dependent manner. Additionally, chlorhexidine was found to inhibit the 17β-estradiol response, with a similar IC50 (2.9 μM). In contrast, the natural terpenes thymol and menthol were found to be competitive antagonists of the receptors; however, their IC50 values were higher (by orders of magnitude). We tried to estimate the risk associated with the presence of these compounds in environmental matrices by calculating hazard quotients (HQs), and the calculated HQs were found to be close to or greater than 1 only when predicted environmental concentrations were used for surface waters.
Keywords: Receptors, Estrogen; T47D-CXCL12; Micropollutants; lidé; Receptors, Androgen; Endocrine disruptive compounds; Recombinant yeast assay; Anti-Bacterial Agents; antibakteriální látky; androgenní receptory; Toothpaste; Mouthwash; receptory pro estrogeny; Humans